2020
DOI: 10.21203/rs.3.rs-58829/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CORO6 Promotes Cell Growth and Invasion of Clear Cell Renal Cell Carcinoma via Activation of WNT Signaling

Abstract: BackgroundRenal cell carcinoma (RCC) constitutes the most lethal type of genitourinary cancer. Understanding of RCC tumor biology helps to identify novel targets and develop directed treatments for patients with this type of cancer. MethodsBioinformatical Analysis of The Cancer Genome Atlas Kidney Renal Clear Cell Carcinoma dataset. Western blotting and qPCR were used to examine the expression levels of interested genes. Flow cytometry, MTT, BrdU staining, wound healing assay and transwell invasion assay were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Additionally, MMP-9 is one of the Wnt pathway target genes, which can be transcriptionally regulated [31]. According to some substantial studies, the WNT/β-catenin pathway is hyperactivated in ccRCC, and targeted inhibition of the WNT/β-catenin pathway may become a feasible therapeutic strategy for tumors [32][33][34]. Here, our results showed that NEK2 silencing could obviously downregulate the protein expression levels of key proteins, such as p-GSK-3β, β-catenin, and the downstream regulator c-Myc, proving that NEK2 silencing could inhibit the WNT/β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, MMP-9 is one of the Wnt pathway target genes, which can be transcriptionally regulated [31]. According to some substantial studies, the WNT/β-catenin pathway is hyperactivated in ccRCC, and targeted inhibition of the WNT/β-catenin pathway may become a feasible therapeutic strategy for tumors [32][33][34]. Here, our results showed that NEK2 silencing could obviously downregulate the protein expression levels of key proteins, such as p-GSK-3β, β-catenin, and the downstream regulator c-Myc, proving that NEK2 silencing could inhibit the WNT/β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%